1999
DOI: 10.1016/s0893-133x(99)00014-7
|View full text |Cite
|
Sign up to set email alerts
|

D-Cycloserine Increases Positive Symptoms in Chronic Schizophrenic Patients When Administered in Addition to Antipsychotics A Double-Blind, Parallel, Placebo-Controlled Study

Abstract: A hypofunction of the glutamatergic system and NMDA receptors in schizophrenia has been hypothesized. Therefore, stimulation of these receptors could be of benefit to patients with schizophrenia. D-cycloserine has been used for this purpose. This study reports the effects of 100 mg D-cycloserine, when added to typical antipsychotics in chronic schizophrenic patients exhibiting prominent negative symptoms, using a placebo-controlled, double-blind, parallel, design. D-cycloserine (Paschen 1996) and schizophr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
47
1

Year Published

2002
2002
2010
2010

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(48 citation statements)
references
References 42 publications
0
47
1
Order By: Relevance
“…With Dcycloserine, doses in excess of 100 mg cause symptom exacerbation due to emergent NMDAR antagonist effects, producing a narrow therapeutic window. 96 Results of clinical trials conducted with NMDAR agonists have been consistent across studies (Table 1). All studies have demonstrated large effect-size (0.9-2.1 SD units) improvement in negative and cognitive symptoms when these agents are added to typical antipsychotics, or newer atypicals.…”
Section: Glutamatergicmentioning
confidence: 62%
“…With Dcycloserine, doses in excess of 100 mg cause symptom exacerbation due to emergent NMDAR antagonist effects, producing a narrow therapeutic window. 96 Results of clinical trials conducted with NMDAR agonists have been consistent across studies (Table 1). All studies have demonstrated large effect-size (0.9-2.1 SD units) improvement in negative and cognitive symptoms when these agents are added to typical antipsychotics, or newer atypicals.…”
Section: Glutamatergicmentioning
confidence: 62%
“…Seven of them (6,12,31-34,47) did not find any significant change in positive symptoms and two (with higher dosages, namely 100 and 250 mg/day) reported worsening of positive symptoms (36,46).…”
Section: D-cycloserine Added To Conventional Antipsychoticsmentioning
confidence: 92%
“…Ten trials evaluated the addition of D-cycloserine to typical antipsychotics (6,12,(31)(32)(33)(34)36,37,46,47). Seven of them (6,12,31-34,47) did not find any significant change in positive symptoms and two (with higher dosages, namely 100 and 250 mg/day) reported worsening of positive symptoms (36,46).…”
Section: D-cycloserine Added To Conventional Antipsychoticsmentioning
confidence: 99%
“…Of the four agents, D-cycloserine has been the least promising, possibly due to its partial agonism and the fact that it acts as an antagonist at high (100 mg) doses. 51 Another proposed approach to rectifying NMDA hypoactivity via glycine allosterism involves the glial glycine transporter GLYT1, which is a reuptake pump that terminates the synaptic action of glycine by shuttling glycine back into glial cells; inhibition of this transporter should theoretically increase the synaptic availability of glycine, thus enhancing NMDA neurotransmission. 52 In this manner, GLYT1 inhibitors are analogous to drugs that inhibit reuptake of other neurotransmitters, such as serotonin selective reuptake inhibitors.…”
Section: Glycine Agonistsmentioning
confidence: 99%